(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Mediation, as used in law, is a formof alternative dispute resolution (ADR), a way of resolving disputesbetween two or more parties with concrete effects. Typically, a third party,the mediator, assists the parties to negotiate a settlement.Disputants may mediate disputes in a variety of domains, such as commercial,legal, diplomatic, workplace, community and family matters. The term"mediation" broadly refers to any instance in which a third partyhelps others reach agreement.